Enhancement of oxaliplatin efficacy and amelioration of intestinal epithelial damage by Lactobacillus rhamnosus GG through modulation of gut microbiota - Zhang, Zijie; Li, Rui; Ren, Yilin; Ni, Yalan; Shen, Xiaoyu; Yi, Deli; Xu, Zheng-hong; Geng, Yan; You, Qingjun (Frontiers in Microbiology, 2025)
BackgroundNon-small cell lung cancer (NSCLC) is a leading cause of cancer-related mortality worldwide, necessitating extensive research into effective treatment strategies. Despite advancements in targeted therapies and immunotherapies, traditional chemotherapy remains the primary treatment modality for most patients. Here, we explored the synergy between Lactobacillus rhamnosus GG (LGG), a probiotic, and the chemotherapeutic drug oxaliplatin (Oxp) in enhancing NSCLC treatment outcomes.MethodsWe utilized a BALB/c nude mouse subcutaneous tumor model to assess the therapeutic impacts of LGG and Oxp. Mice were randomized into five groups: negative control, model control, Oxp, LGG, and LGG + Oxp treatment groups. The main outcomes assessed included tumor weight and volume, histopathological changes, and gene expression via qRT-PCR. The gut microbiota composition was examined by 16s rRNA gene sequencing.ResultsThe combined treatment of LGG and Oxp significantly reduced tumor weight and volume, and improved tumor-associated pathological changes compared to the model group. The LGG treatment also alleviated Oxp-induced intestinal damage and inflammation, maintaining intestinal barrier integrity. The combined treatment modulated genes linked to intestinal barrier function and inflammation, upregulated Occludin and Mucin2, and downregulating Tnf-α and Il-1β in colon tissues. Gut microbiota analysis showed notable shifts following treatment. Specifically, the Oxp group exhibited a decrease in Clostridium_XlVa and an increase in Desulfovibrio, indicating a shift in microbial balance. The relative abundance of Lactobacillus increased significantly in the combined treatment group compared to the control, suggesting a potential probiotic effect. The combined treatment also restored some of the microbial communities, such as Bacteroidaceae resembles the Bacteroidetes, Bacteroidia, and Bacteroidales in the NC group, which were reduced by Oxp treatment alone.ConclusionThe combined use of LGG and Oxp offers a promising therapeutic strategy for NSCLC, warranting further investigation into the interplay between probiotics, chemotherapy, and the gut microbiota.